Cell-derived Microparticles Circulate in Healthy Humans and Support Low Grade Thrombin Generation - Berckmans, René J.; Nieuwland, Rienk; Böing, Anita N.; Romijn, Fred P. H. T. M.; Hack, C. Erik; Sturk, Augueste (Thrombosis and Haemostasis, 2001)
We determined the numbers, cellular origin and thrombin-generating properties of microparticles in healthy individuals (n = 15). Micro-particles, isolated from fresh blood samples and identified by flow cytometry, originated from platelets [237106/L (median; range 116-565)], erythrocytes (28106/L; 13-46), granulocytes (46106/L; 16-94) and endothelial cells (64106/L; 16-136). They bound annexin V, indicating surface exposure of phosphatidylserine, and supported coagulation in vitro. Interestingly, coagulation occurred via tissue factor (TF)-independent pathways, because antibodies against TF or factor (F)VII were ineffective. In contrast, in our in vitro experiments coagulation was partially inhibited by antibodies against FXII (12%, p = 0.006), FXI (36%, p <0.001), FIX (28%, p <0.001) or FVIII (32%, p <0.001). Both the number of annexin V-positive microparticles present in plasma and the thrombin-generating capacity inversely correlated to the plasma concentrations of thrombin-antithrombin complex (r = -0.49, p = 0.072 and r = -0.77, p = 0.001, respectively), but did not correlate to prothrombin fragment F1+2 (r = -0.002, p = 0.99). The inverse correlations between the number of microparticles and their thrombin-forming capacity and the levels of thrombin-antithrombin complex in plasma may indicate that microparticles present in the circulation of healthy individuals have an anticoagulant function by promoting the generation of low amounts of thrombin that activate protein C. We conclude that microparticles in blood from healthy individuals support thrombin generation via TF- and FVII-independent pathways, and which may have an anticoagulant function.
Keywords: Microparticles; coagulation; thrombin generation; flow cytometry; tissue factor